2017
DOI: 10.5901/mjss.2017.v8n3p27
|View full text |Cite
|
Sign up to set email alerts
|

A Cross Sectional Study on HIV Risk Perception and Sexual Behaviours among Commercial Motorcyclists in Makurdi, Benue State Nigeria

et al.

Abstract: The study was aimed at determining the HIV risk perception and sexual behaviour among commercial motorcyclists in Makurdi

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
6
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 10 publications
3
6
2
Order By: Relevance
“…This finding aligned with reports from a 2017 National health survey, which showed that only 28.6% of young people aged 15-24 could correctly identify ways of preventing sexual transmission of HIV (26). This raises a cause for concern because young people in Nigeria are among the most vulnerable group due to several reasons including their likelihood to engage in risky sexual behavior and low HIV risk perception (27,28,29). The majority of the participants (92.4%) had not taken nPEP before because they have not been exposed while 74 (20.3%) did not take because of fear and stigmatization.…”
Section: Discussionsupporting
confidence: 81%
“…This finding aligned with reports from a 2017 National health survey, which showed that only 28.6% of young people aged 15-24 could correctly identify ways of preventing sexual transmission of HIV (26). This raises a cause for concern because young people in Nigeria are among the most vulnerable group due to several reasons including their likelihood to engage in risky sexual behavior and low HIV risk perception (27,28,29). The majority of the participants (92.4%) had not taken nPEP before because they have not been exposed while 74 (20.3%) did not take because of fear and stigmatization.…”
Section: Discussionsupporting
confidence: 81%
“…This high knowledge prevalence might be due to study population restriction to secondary school adolescents who constitute the largest proportion of young adults who are sexually active. Unlike the results of a study in Ekiti State [21] where the key sources of information were Television/radio, internet and magazines, findings of other studies carried out among adolescents both within and outside the country reported that major sources of information about STIs were school lessons, hospital/clinic, mass media, and health magazines [20,22] this study's major source of information for STIs were from Teachers 78(26.4%) followed by Radio/television 52(17.5%) and Internet 48(16.2%) aligns with findings from the study conducted in Zaria (20).…”
Section: Discussioncontrasting
confidence: 65%
“…54 This raises a cause for concern because young people in Nigeria are among the most vulnerable group due to several reasons including their likelihood to engage in risky sexual behavior and low HIV risk perception. 4,40,55 Also young women aged 15-24 are almost twice as likely to be infected with HIV as their male counterparts in Nigeria. 26 This is similar to other parts of Sub-Saharan Africa where incidence rate of HIV infections among young women aged 15-24 were significantly higher than among young men of the same age.…”
Section: Discussionmentioning
confidence: 99%